2021
DOI: 10.1186/s12909-020-02479-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining competence profiles of different medical specialties with the requirement-tracking questionnaire – a pilot study to provide a framework for medial students’ choice of postgraduate training

Abstract: Background The medical specialties are characterised by a great diversity in their daily work which requires different sets of competences. A requirement analysis would help to establish competence profiles of the different medical specialities. The aim of this pilot study was to define competence profiles for individual medical specialties. This could provide a framework as support for medical graduates who wish to choose a medical specialty for their postgraduate training. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Questionnaires for job requirements should be able to differentiate between different occupations. Previous studies with the R-Track questionnaire revealed differences between medical specialties [ 17 , 20 ], which were in line with the expected differences. For this study, we adapted the R-Track questionnaire to be used for self-assessment of the respective competence facets (Supplement 1 ).…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…Questionnaires for job requirements should be able to differentiate between different occupations. Previous studies with the R-Track questionnaire revealed differences between medical specialties [ 17 , 20 ], which were in line with the expected differences. For this study, we adapted the R-Track questionnaire to be used for self-assessment of the respective competence facets (Supplement 1 ).…”
Section: Methodssupporting
confidence: 86%
“…Students who wish to choose paediatrics rated “Sensory abilities” lowest, whereas students who want to choose anaesthesiology or internal medicine rated “Psychomotor & multitasking abilities” lowest. Comparing medical students’ competence profiles with the competence profiles defined by physicians working in these three specialties [ 20 ], the competence profiles showed 100 % congruence for internal medicine, 33.3 % for paediatrics, and 0 % for anaesthesiology (Table 1 ). The differences between the highest, and lowest mean of the six competence areas within each group were 0.53 (students) versus 0.98 (physicians) for internal medicine, 0.43 (students) versus 0.93 (physicians) for paediatrics, and 0.66 (students), and 0.75 (physicians) for anaesthesiology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations